The Influence Of Eyes And Brain Behind "Arterma Tool" In First Person Point Of View Interface Of Games - Irma Shayana, Samaden; Azizah, Jaafar; Irza Shayani, Samaden (2014)
The application of point of view (POV) in electronic games has been vastly applied and fast becoming a favorite among electronic games (EG) players particularly in games of action genre like warfare games. While allowing the users to experience the character first-hand, POV has its limitations for users. One example of the problems is the difficulty to anticipate the direction an attack by the enemy from a POV blindspot. Another problem is the difficulty to prepare a strategy. Some players become “somewhat dizzy” and eventually give up the game. This paper elaborates on the development of a framework for interactive montage on EG software interface using ArTerma tools and how the ArTerma tool works in the POV interface. Therefore, to accomplish the development of ArTerma tools, (A1(DDI)2E3) model is used. In (A1(DDI)2E3) model usage, ADDIE model is combined with other model concept such as “Diegesis-Spatiality” concept Model, Frame concept model, and Mental concept model has been employed along side an elaboration on case studies. The study hopes that the developed a new model as well as support tool can help improve future EGs.